What role do credit cards play in impulse buying? - Rizaldi, Herna; Arifiyanto, Muhammad; Hidayah, Nur Laili (Economics and Business International Conference Proceeding, 2024)
This research aims to determine the mediating role of credit card use on the relationship between hedonic motivation and promotional programs on the impulse purchases of online and offline store consumers. This quantitative research was conducted in Pekalongan, Central Java, Indonesia, with a total of 92 credit card user respondents collected using purposive random sampling. The data was processed using Partial Least Square, the results that hedonic motivation has no effect on impulsive buying, promotional programs has a positive and significant effect on impulsive buying, hedonic motivation and promotional programs has a positive and significant effect on credit card use, credit card use has a positive and significant effect on impulsive buying , credit card use has a full mediating role in the relationship between hedonic motivation and impulsive buying and partial mediation in the relationship between promotional programs and impulsive buying.